Athletes' knowledge and views on OTC medication - Mottram, D.; Chester, N.; Atkinson, G.; Goode, D. (International Journal of Sports Medicine, 2008)
A questionnaire was administered to elite athletes from Australia, Canada, the UK, and the USA representing 10 Olympic sports in order to explore knowledge and understanding of over-the-counter (OTC) medication since the removal of many of these substances from the World Anti-Doping Agency (WADA) Prohibited List, in 2004. Athletes demonstrated limited knowledge and understanding. Around half (50.5 %) knew the penalty incurred following a doping violation involving a banned OTC stimulant. The terms Monitoring Program and Specified Substance List were understood by 43.3 % and 67.5 % of respondents, respectively. Overall, the status of substances in relation to the Prohibited List was correctly identified in just 35.1 % of cases. As a whole, athletes were of the opinion that OTC stimulants posed a risk to health, were performance enhancing and that their use was against the spirit of sport. They were undecided as to whether these drugs should be returned to the Prohibited List. Elite athletes require targeted education programmes that will enable them to make informed decisions on the potential of OTC medications for therapeutic or performance enhancing purposes.